-3+6x=40+5x

Simple and best practice solution for -3+6x=40+5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3+6x=40+5x equation:


Simplifying
-3 + 6x = 40 + 5x

Solving
-3 + 6x = 40 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-3 + 6x + -5x = 40 + 5x + -5x

Combine like terms: 6x + -5x = 1x
-3 + 1x = 40 + 5x + -5x

Combine like terms: 5x + -5x = 0
-3 + 1x = 40 + 0
-3 + 1x = 40

Add '3' to each side of the equation.
-3 + 3 + 1x = 40 + 3

Combine like terms: -3 + 3 = 0
0 + 1x = 40 + 3
1x = 40 + 3

Combine like terms: 40 + 3 = 43
1x = 43

Divide each side by '1'.
x = 43

Simplifying
x = 43

See similar equations:

| 2x-5=28 | | -4+6x=180-2x | | 4-10x=22-4x | | -(5y+4)-(-4y-7)=3 | | 4=m-11 | | 14+3a=-2a-1 | | 8+5x=80+x | | y=4x+3 | | 4-3x=-35+10x | | 4-3x=-35+16x | | 9(2x-1)=3(6x+3) | | 9+x=-3 | | 9+z=-3 | | 0=3x^3+11x^2-4x | | 63-x=-2+4x | | 3+19t-1=8t+36-6t | | 4-2x=-16+3x | | 4-2x=-16+2x | | Z^2+3z=-2 | | z+9=2 | | 41+3x=14+6x | | -7.1x=49.7 | | q-2=-q+1 | | 50-4x=4-2x | | 12t=-39 | | n-5=-2 | | 12-7x=60-21x | | 61-3x=1+9 | | 8m=-24 | | n+36=49 | | 2m=-24 | | n+16=22 |

Equations solver categories